Employees: Invisible added value of a company - Magda Zupančič (Naše gospodarstvo / Our Economy, 2018)
In developed economies, where the work input exceeds the physical input, the lack of harmonised and standardised rules of human capital assessment is visible. The mentioned indicates the deficit of an important part of the comprehensive value-added assessment. What do we lose by ignoring the important part of the employee's value added in the working process? Companies underestimate the employee's human capital input. Consequently, society typically does not recognize invisible sources of value added in companies. The goals of this article are to highlight the missing human capital (HC) element at the company level assessment and to raise the awareness about its importance. By analysing existing methods of coping with the mentioned challenge, no harmonised solution is evident. By the increasing share of the service sector, emphasis on the HC element should be monitored more closely. The article focuses on the missing and invisible human capital elements in the framework of the value added; it offers suggestions for inclusion of the human capital factor in the process of company's value added assessment as well as reflections on further steps in this direction.
Keywords: J24; 330; employee; value added; human capital; assessment